Program Peduli dan Berbudaya Lingkungan Hidup di Sekolah (PBLHS) SDN 183 Pekanbaru sebagai sekolah Adiwiyata nasional - Riyanda Putra; Sukendi; Muhammad Syafi'i (EcoNews, 2022)
This research was conducted at SDN 183 Pekanbaru City which aims to evaluate the planning and implementation of the environmental care and cultured movement towards PBLHS planning at the 183 Public Elementary School Pekanbaru. The methodology used is a qualitative method with a descriptive approach. The procedure for collecting data is through a survey method with interview techniques, observation and using a questionnaire. The population in this study were all elements in the school, with a total sample of 100 people. Analysis of the data used in this study is using the validity test and reliability test. The results of this study indicate that policies on environmental protection and management made by the government through education will be implemented well by achieving the Adiwiyata award. The implementation of the school environmental culture program (PBLHS) stimulates students in the spirit of developing environmentally-based schools by 90%. The success of this program can be seen from the enthusiasm of the students in developing Adiwiyata schools, preserving TOGA, as well as the clean and healthy Saturday program.